Comunicação e conversão: uma análise do uso do WhatsApp® por lojas de vestuário masculino para clientes de alta renda - Silva, Renan Nogueira (2024)
Brazil has more than 147 million accounts registered on WhatsApp® (data from 2023), which allows for greater communication between companies and their consumers, but there is still a lack of academic research on this type of technology. The main objective of this research is to understand whether interactions via WhatsApp® between customer and store (brand) interfere with long-term purchases. For the research, an existing database from a CRM (Customer Relationship Management) technology company was used. The data refers to a men's clothing retail brand aimed at a public with high purchasing power (due to the price of its products). This research adopted a quantitative methodological approach and the analysis included information about male consumers, aged between 25 and 54, who had already purchased from the retailer in Brazil. The total organized base is 1142 consumers who purchased in one of the brand's 20 stores, spread across 10 Brazilian states. The data covers the period from June 2021 to January 2024. Using the Eviews® software, the relationship between “contact” and “purchase” was analyzed, as well as the impact of this relationship. The results demonstrated that there is a positive relationship between contact (which the brand makes via WhatsApp® with the consumer) and the purchase; and that 4,258 contacts are needed to have an impact on the purchase. These results help brands to be more assertive in their communications with their consumers, and avoid excessive messages, reducing costs and improving consumer perception by reducing SPAM.